Translation universals : do they exist? - Mauranen, Anna; Kujamäki, Pekka (Benjamins translation library, 2004)
Translation universals is one of the most intriguing and controversial topics in recent translation studies. Can we discover general laws of translation, independent of the particularities of individual translations? Research into this is new: serious empirical work only began in the late nineties. The present volume offers the state of the art on the issue. It includes theoretical discussion on alternative conceptualisations and new distinctions around the basic concepts. Several papers test hypotheses on universals in the light of recent work in different languages, and some suggest new ones.